2013
DOI: 10.1364/boe.5.000069
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution visualization of mouse cardiac microvasculature using optical histology

Abstract: Cardiovascular disease typically is associated with dysfunction of the coronary vasculature and microvasculature. The study of cardiovascular disease typically involves imaging of the large coronary vessels and quantification of cardiac blood perfusion. These methods, however, are not well suited for imaging of the cardiac microvasculature. We used the optical histology method, which combines chemical optical clearing and optical imaging, to create high-resolution, wide-field maps of the cardiac microvasculatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…11,12 Briefly, this method first involved cardiac perfusion of the lipophilic fluorescent dye DiI to label the mouse microvasculature, followed by tissue harvest and preparation similar to the procedure previously described. All procedures were approved by the Institutional Animal Care and Use Committee at University of California, Irvine.…”
Section: Optical Histologymentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Briefly, this method first involved cardiac perfusion of the lipophilic fluorescent dye DiI to label the mouse microvasculature, followed by tissue harvest and preparation similar to the procedure previously described. All procedures were approved by the Institutional Animal Care and Use Committee at University of California, Irvine.…”
Section: Optical Histologymentioning
confidence: 99%
“…The result is that both techniques are more challenging to implement than simply immersing the tissue in an optical clearing agent. We recently described a method that we call optical histology, 11,12 which involves applying optical clearing using FocusClear to thick (∼1 mm) tissue sections and subsequent imaging with confocal fluorescence microscopy. With optical histology, we demonstrated high-resolution visualization of fluorescent structures up to depths of 500 to 700 μm within each section.…”
Section: Introductionmentioning
confidence: 99%
“…Despite advancements in the field, our understanding of the adult heart structure and its remodeling following disease is still limited by the inability to provide three-dimensional (3D) images of the myocardium at cellular resolution. There is a growing trend to study the 3D structure of organs and tissues, requiring researchers to work with volumes rather than thin sections [3]. Confocal microscopy is a well-established imaging technique that plays an important role in studying tissue with high magnification.…”
Section: Introductionmentioning
confidence: 99%
“…For the last decade, optical clearing technique to improve the imaging depth has been actively investigated [21][22][23][24][25][26][27][28][29][30][31][32][33][34]. As the mismatch in refractive index (RI) between cellular components in tissue is the major cause of light scattering, selective removal of cellular components with relatively low or high refractive index can reduce the light scattering and make the tissue more optically transparent.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently used approach is replacing interstitial fluids (RI~1.33) in inter-and intra-cellular space with optical clearing agents (OCAs) which have refractive indices of ~1.46, matched to the average refractive index of most biological samples. It has been demonstrated that several OCAs such as glycerol [26- [30][31][32] and BABB [33] can enhance imaging depth in various organs such as brain [22][23][24][25][26], skin [27][28][29], pancreas [30], colon [31] and heart [32][33][34]. However, optical clearing effect of OCAs on LN has not yet been clearly demonstrated.…”
Section: Introductionmentioning
confidence: 99%